2013
DOI: 10.1177/0956797612459660
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Multitasking Reflect Spatial Ability

Abstract: Demands involving the scheduling and interleaving of multiple activities have become increasingly prevalent, especially for women in both their paid and unpaid work hours. Despite the ubiquity of everyday requirements to multitask, individual and gender-related differences in multitasking have gained minimal attention in past research. In two experiments, participants completed a multitasking session with four gender-fair monitoring tasks and separate tasks measuring executive functioning (working memory updat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
121
5
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(141 citation statements)
references
References 33 publications
11
121
5
4
Order By: Relevance
“…As research on eyeblink startle in response to different types of interoceptive stimulation (and esophageal and other gastrointestinal sensations in particular) has just started recently, no conclusions can yet be drawn as to the underlying mechanism responsible for the difference between startle in response to esophageal stimulation as found in the current study, versus that to respiratory stimulation as found in previous studies Pappens et al, 2010;2013). Nevertheless, exploration, description, and replications of the typical startle response occurring during different types of interoceptive stimulation may help elucidate the differential responding upon interoceptive versus exteroceptive threat.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…As research on eyeblink startle in response to different types of interoceptive stimulation (and esophageal and other gastrointestinal sensations in particular) has just started recently, no conclusions can yet be drawn as to the underlying mechanism responsible for the difference between startle in response to esophageal stimulation as found in the current study, versus that to respiratory stimulation as found in previous studies Pappens et al, 2010;2013). Nevertheless, exploration, description, and replications of the typical startle response occurring during different types of interoceptive stimulation may help elucidate the differential responding upon interoceptive versus exteroceptive threat.…”
contrasting
confidence: 57%
“…An argument in favor of women but not men being able to simultaneously process the startle probe and the visceral stimulus, is that women generally outperform men in multitasking (Jing et al, 2012;Mäntylä, 2013;Ren et al, 2009), although not always (Buser and Peter, 2012). Men on the other hand outperform women on monitoring accuracy (Mäntylä, 2013), and early research on visceral perception also suggests men are generally more accurate perceivers of interoceptive sensations (Pennebaker and Roberts, 1992). For our study, this then implies that perhaps men were solely focused on monitoring their internal state, and this prevented them from being responsive to the startle probe.…”
Section: Discussionmentioning
confidence: 99%
“…The novelty of our study is not only the relatively large number of participants, but also the good gender balance. Despite the few studies about gender differences in multi-tasking, there has been an interesting discussion very recently about a study by Mäntylä (2013) which received much attention. Probably the main reason for the attention in the media for this study was the conclusion that men performed better than women in a multi-tasking paradigm.…”
Section: Relation To Other Workmentioning
confidence: 99%
“…The idea that women are better multi-taskers than men is commonly held by lay people (for a review see Mäntylä 2013). While the empirical evidence for women outperforming men in multi-tasking has been sparse, researchers have shown that women are involved more in multi-tasking than men, for example in house-hold tasks (Offer and Schneider 2011;Sayer 2007).…”
Section: Introductionmentioning
confidence: 99%
“…2013, Mäntylä, 2013. Bu çalışmanın çıkış noktası olan bu durum göz önünde bulundurularak matematik öğretmenliği ya da matematik bölümlerinde okuyan öğrencilerin klasik uzamsal görselleştirme sorularının yanı sıra matematik alanına özgü sorularla da bu yeteneğinin belirlenmesi amaçlanmıştır.…”
Section: Sonuç Ve Tartışmaunclassified